2010
DOI: 10.1093/jjco/hyq030
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of a Disintegrin and Metalloprotease-9 in Hepatocellular Carcinoma: Implications for Tumor Progression and Prognosis

Abstract: A disintegrin and metalloprotease-9 is over-expressed in hepatocellular carcinoma tissues, consistent with findings in other tumor entities, and is an independent prognostic marker of overall survival following hepatectomy. Further studies are needed to investigate the precise function of a disintegrin and metalloprotease-9 in the progression of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…In this study, a significant increase in ADAM9 protein expression in OSCC tissues, compared with in normal oral tissues, was demonstrated by immunohistochemistry, a finding that agrees with the results of other prior studies, which demonstrated ADAM9 protein overexpression in various types of cancer (9,15,17,18,(20)(21)(22)(23)25,26). Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, a significant increase in ADAM9 protein expression in OSCC tissues, compared with in normal oral tissues, was demonstrated by immunohistochemistry, a finding that agrees with the results of other prior studies, which demonstrated ADAM9 protein overexpression in various types of cancer (9,15,17,18,(20)(21)(22)(23)25,26). Though particularly in squamous cell carcinoma, ADAM9 protein overexpression is also present in cancer of the cervix, the esophagus, the pharynx, the larynx, and the skin around the head and neck region (9,21,25,26).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, ADAM9 can function in both physiological and pathological conditions. Regarding its involvement in pathologic conditions, ADAM9 overexpression has been identified in a variety of cancer types, including breast cancer (16), renal cancer (17), prostate cancer (18), skin melanoma (19), uterine cervical cancer (20,21), hepatocellular carcinoma (22), non-small cell lung cancer (23), colon cancer (24), gastric cancer (15), esophageal cancer (25) and head and neck squamous cell carcinoma (HNSCC) (26). In the oral cavity, conflicting results of chromosomal aberrations in the ADAM9-containing region have been identified by the array comparative genomic hybridization technique (9,27).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, overexpression of ADAM9 in lung cancer cells resulted in both brain and lung metastases, whereas mock-transfected cells only colonized the lungs (37,38). All these results are in accordance with clinical observations indicating that expression of ADAM9 was correlated with shortened survival and poor outcome of cancer patients and associated with the occurrence of distant metastases (39)(40)(41). ADAM9 was reported to be expressed by several malignancies, including renal, prostate, thyroid, gastric, breast, and non-small-cell lung cancer cells, highlighting its potentially broader importance in neoplasia (38,39,(42)(43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 85%
“…ADAM9, a member of the ADAM family, has been demonstrated to be upregulated in a range of types of human cancer, including renal cell cancer (35), prostate cancer (36), breast cancer (37), hepatocellular carcinoma (38), and pancreatic cancer (39). Previous studies have also identified miRNAs that may interact with ADAM9.…”
Section: Discussionmentioning
confidence: 99%